Unified tax incentive policies, tax burden fairness, and corporate investment efficiency - Xiaoyang Zhao; Guangyuan Ma; Feng Guan (China Journal of Accounting Studies)
The implementation of unified tax incentive policies across China is a core issue for effectively advancing the creation of a unified national market and is related to how to effectively promote high-quality development of enterprises. Exploiting the issuance of the Notice on Cleaning up and Regulating Preferential Taxation Policies, this study empirically examines the impact of unified tax incentive policies on the investment efficiency of micro-enterprises. The results reveal that by promoting fair competition among enterprises and curbing managerial shirking behaviour, these policies help companies improve their investment efficiency. Cross-sectional tests indicate that the main effect is more pronounced in companies with poorer operating performance and weaker market competitiveness.